Peran Sekolah Peternakan Rakyat dalam Meningkatkan Nilai Tambah pada Peternak Sapi Potong di Kabupaten Muara Enim - Oktavia, H. C.; Cahyadi, E. R.; Syamsun, M. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The gaps issue in the food commodity happens in Muara Enim District, the demand for beef were steadily increasing but it can’t fulfilled by the amount of beef production in the area. In order to increase the quality, population and productivity that based on the local farmer, government decide to make an effort to increase local farmer business by establishing the Sekolah Peternakan Rakyat (SPR). The purpose of this research was to analyze the effect of SPR for the local farmer in Muara Enim by mapping beef cattle supply chain and analyzing the role of SPR to increase added value for local farmer in Muara Enim. Primary data was collected by conducting an interview to respondents with a questionnaire as its guidelines. The data was analyzed by Hayami method. The result of this research shows that the SPR farmer had more wide sale access compared to non SPR farmer and SPR farmer added value increase can be seen by the improvement of the cattle weight.